Windows Server 2016 administration cookbook : core infrastructure, IIS, Remote Desktop Services, Monitoring, and Group Policy - Krause, Jordan (Packt Publishing, 2018)
Windows Server 2016 is an operating system designed to run on servers. It supports enterprise-level data storage, communications, management, and applications. This book contains specially selected, detailed help on core, essential administrative tasks of Windows Server 2016.